First and second sound in disordered strongly nonlinear lattices: numerical study. (13th August 2015) - Pikovsky, Arkady
Abstract: We study numerically secondary modes on top of a chaotic state in disordered nonlinear lattices. Two basic models are considered, with or without a local on-site potential. By performing periodic spatial modulation of displacement and kinetic energy, and following the temporal evolution of the corresponding spatial profiles, we reveal different modes which can be interpreted as first and second sound.